HUBUNGAN KEMANDIRIAN TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA DI KELAS X SMK KOTA CIMAHI - Novia Handayani; Fauziah Hidayat (Journal on Education, 2019)
This research aims to look at the relationship of independence of learning with student learning outcomes. The methods used in this research is descriptive qualitative method method. As for the sample in this research is a class X students amounted to 33 students consisting of 31 male students and 2 female students. Determination of class in this research was conducted with a random techniques adapted to the teaching schedule of teachers in the learning of mathematics. Data collection is done using the giving question form and test. Based on the research results obtained by the conclusion that: there is a relationship between the independence of the student learning and the results of his studies. The relationship between the independence of the study with the results of the study of mathematics is the higher level learning independence it will be increasingly higher learning results. Vice versa the lower the level of independence of learning it will be getting lower also the results of the study. As for some of the students that the results of their learning independence is low but higher learning outcomes it is influenced by factors: at the time of the test students fill put by cheating on their friends and attitudes learning independence high results with low learning outcomes then the factors that affected students are able to deal with the problems that exist, but it is not dependent upon his friend this shows the high independence of the study.